Ispol'zovanie nejrobioupravlenija v trenirovocnom i obrazovatel'nom processach - Cerapkina, L. P.; Bayova, N. A.; Talamova, G. I.; Tristan, V. G. (Teorija i Praktika fiziceskoj Kul'tury, 2006)
Authors have set as the purpose the perfection of brain mechanisms at the persons actively engaged in physical culture and sports, with the use of the EEG-BF training.